Optimalisasi Promosi Kesehatan Rumah Sakit dalam Mewujudkan Gerakan Masyarakat Hidup Sehat Berkemajuan di Rumah Sakit Muhammadiyah - Emma Rachmawati; Mochamad Iqbal Nurmansyah; Betty Semara Laksmi; Yuyun Umniyatun; Lia Kharisma Saraswati (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2019)
Nowadays, Indonesia faces a problem with infectious and non-infectious diseases. To implement a collaborative health program, this assistance activity involved the community, the General Health Advisory Council PP Muhammadiyah, and Ministry of Health, Indonesia to implement the Healthy Life Movement. Mentoring activities took place from July to November 2018 by using partnership method. The partnership facilitates Health Volunteers to implement HPH outside of Hospital and develop health promotion media for the implementation of HPH. The tools for promotion are posters, leaflets, manual fans, and guidelines for measuring nutrition. This health promotion is the implementation form of Healthy Life Movement for the community. HPH programs have been carried out in various areas, they are 6 Muhammadiyah Hospitals in 4 provinces of Indonesia